An interesting 1, 4, 2, 5-dioxadiazine-furazan system: structural modification by incorporating versatile functionalities. Issue 41 (11th October 2017) - Yu, Qiong; Cheng, Guangbin; Ju, Xuehai; Lu, Chunxu; Lin, Qiuhan; Yang, Hongwei
Abstract : An N -trinitroethylamino derivative and amminonium salt based on the 1, 4, 2, 5-dioxadiazene-furazan system are synthesized and characterized. Due to their layer-by-layer structure, these two compounds show good thermal stabilities and low sensitivities. Abstract : Herein, the 1, 4, 2, 5-dioxadiazine ring is combined with two furazan rings. Interestingly, the structure of the 1, 4, 2, 5-dioxadiazine-furazan system can be modified by incorporating versatile functionalities. The N -trinitroethylamino functionalization derivatives and energetic salts based on 3, 6-bis(4-amino-1, 2, 5-oxadiazol-3-yl)-1, 4, 2, 5-dioxadiazine are investigated. Derivatives of these functionalities are synthesized and fully characterized via multinuclear NMR spectroscopy, IR spectroscopy, and elemental analysis. The structures of compounds1–7 are further confirmed by single-crystal X-ray diffraction. Compounds1–12 have moderate thermal stabilities (143–177 °C, except2 (114 °C), and3 (88 °C)) and exhibit acceptable sensitivities (IS 3.52–16.3 J and FS 100–240 N). Based on the measured densities (1.73–1.95 g cm −3 ) and heats of formation (573.5–2065.4 kJ mol −1 ), the detonation velocities ( D 8519–9563 m s −1 ) and pressures ( P 29.3–43.3 GPa) are calculated. Among them, the trinitroethylamino derivative1 and ammonium salt of 3, 6-bis(4-nitroamino-1, 2, 5-oxadiazol-3-yl)-1, 4, 2, 5-dioxadiazine5 show a layered assembly of the 1, 4, 2, 5-dioxadiazine-furazan system. These two compounds show good thermal stabilities (1, 154 °C and5, 177 °C) and relatively low sensitivities (1, 16.3 J and5, 13.4 J). These properties indicate that the layer assembly structure is helpful to improve the thermal stabilities and result in low sensitivities for the corresponding compounds.